The Potential of Red Watermelon Extract as Teeth Whitening Toothpaste - Marahaini, Nur Azizah; Arumnada, Ghania; Masyithoh, Dini Amalia Dewi; Setyawati, Any (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction – The teeth are composed of enamel, dentine, pulp, and cementum. The enamel of the tooth contains hydroxyapatite crystals [Ca10(PO4)6(OH)2] which are small in size and allow for the transfer of ions in chromogen substances causing discoloration of the teeth. Tooth discoloration will eliminate the aesthetic value of the individual's appearance. The use of chemicals and abrasive materials contained in conventional toothpaste in whitening teeth can cause side effects in the form of irritation of the oral mucosal tissue and abrasion of the surface of the teeth, so a safe natural treatment is required. Malic acid in red watermelon (Citrullus lanatus) is a powerful oxidizer that can be used to whiten teeth. Methodology/Approach – Data source search is done using the Google Scholar, Pubmed, and Science Direct search engine with Medical Subject Headings and selected for publication in the past five years. Findings – The principle of dental whitening is oxidation reaction between whitening agent and chromogenic factor, regardless red watermelon has a malic acid as a powerful oxidizer and can be used to whiten teeth. Implication – Home and office dental whitening with carbamide or hydrogen peroxide can cause dental sensitivity. There is a new bleaching proposal without the use of chemical ingredients, thus reducing post-treatment sensitivity. Red watermelon has such a whitening toothpaste with natural ingredients.